Implementasi Program Pembangunan Perumahan dan Lingkungan Desa Terpadu (P2LDT) - Mona Erythrea Nur Islami (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2008)
A house is one of the people’s primary needs. However, people in the rural area sometimes do not realize the importance of a proper house to live in. The government through integral settlement and rural environment developing program has been trying to change the perspective of rural people. The success of this program depends on how the people make it so that this program is always in progress and continuity takes place